1993
DOI: 10.1530/jrf.0.0980393
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of secretion of GnRH in vitro to changes in pituitary concentrations of LH and FSH and serum concentrations of LH during lactation in sows

Abstract: The objectives of this study were (1) to determine whether release of GnRH in vitro was related to concentrations of LH and FSH in serum and pituitaries and to oestradiol in serum of sows at mid- or late lactation, and (2) to determine whether weaning at mid-lactation changes concentrations of these hormones from values expected at mid-lactation to values expected at late lactation. Multiparous crossbred sows were killed on day 14 (n = 5) or day 28 (n = 5) of lactation or on day 14 post partum after litters ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 0 publications
7
22
0
2
Order By: Relevance
“…Com o desmame e a ausência de estímulo por parte dos leitões, o mecanismo de retroalimentação, que inibia a liberação de gonadotrofinas durante a lactação, é removido. Desta forma, o crescimento de folículos ovarianos se acelera e os níveis sangüíneos de estrogênio aumentam, estimulando a ocorrência do cio e a descarga de LH, que desencadeia a ovulação (Sesti & Britt, 1993).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Com o desmame e a ausência de estímulo por parte dos leitões, o mecanismo de retroalimentação, que inibia a liberação de gonadotrofinas durante a lactação, é removido. Desta forma, o crescimento de folículos ovarianos se acelera e os níveis sangüíneos de estrogênio aumentam, estimulando a ocorrência do cio e a descarga de LH, que desencadeia a ovulação (Sesti & Britt, 1993).…”
Section: Resultsunclassified
“…De acordo com Koketsu et al (1996), a diminuição da quantidade ingerida de nutrientes influencia potencialmente o estado metabólico e, portanto, a eficiência reprodutiva da fêmea durante a lactação e após o desmame. Kunavongkrit et al (1983) afirmam que o período para que a involução uterina ocorra é de duas semanas e, segundo Sesti & Britt (1993), nas duas primeiras semanas de lactação, os níveis de LH hipofisário são baixos e insuficientes para estimular a ovulação e a luteinização dos folículos. Assim, um período mínimo de dias em lactação é requerido após o parto para a estabilização do sistema hipotálamo-hipófise-ovário.…”
Section: Resultsunclassified
“…Indeed, in a previous study [1] we reported that GnRH turnover rate, as estimated indirectly by proportion of residual GnRH released in vitro, increased from mid-(Day 14) to late (Day 28) lactation in multiparous sows.…”
Section: Introductionmentioning
confidence: 82%
“…Tissue concentrations of GnRH, as measured at a single point in time in the hypothalamus (preoptic area, medial basal hypothalamus, and stalk median eminence), do not change during lactation in the pig [1]. LH and FSH in blood are relatively low through the first 3-4 wk of lactation in sows and increase thereafter.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation